Intensificação da regeneração motora com peptídeo mimético de HNK-1 e ácido ursólico após avulsão e reimplante de raízes ventrais medulares em camundongos C57BL/6J : Intensification of motor regeneration with HNK-1 mimetic and ursolic acid peptide after avulsion and reimplantation of spinal ventral roots in C57BL/6J mice - Silva, Natália Scanavachia, 1996- (2023)
Orientadores: Alexandre Leite Rodrigues de Oliveira, Luciana Politti Cartarozzi